The Effect of Health Promotion Through Video Media on The Utilization Of Family Medical Plans (Toga) In Heart Disease - Ginting, Rosita; Irmayani; Bangun, Sri Melda; Parinduri, Anggi; Ginting, Luci (JURNAL KESMAS DAN GIZI (JKG), 2024)
Heart disease is recognized globally as a leading cause of death, demanding innovative prevention strategies to reduce the risk of heart disease. One promising approach is the use of Family Medicinal Plants (TOGA), which offers an alternative treatment to combat this disease. In the context of health promotion, media, particularly video, has emerged as an effective tool for raising awareness and encouraging the adoption of better health practices. This study was conducted at one of the hospitals in Lubuk Pakam, Deli Serdang Regency focused on the influence of health promotion via video on the use of TOGA by heart disease patients. Using a Pre-Experimental One Group Pre-test and Post-test design, this study involved 38 heart disease patients selected through purposive sampling. Data analysis was carried out using a paired sample t-test, showing a significant increase in the use of TOGA after health promotion through video media, with the average score increasing from 13.97 to 17.42. The research findings show a p value = 0.000 which confirms that health promotion through video media has a positive impact on the use of TOGA among heart disease patients. This suggests that video, as a health information tool, has great potential to increase acceptance and implementation of TOGA not only among heart disease patients but also in the wider community, offering an effective and accessible strategy to support heart health.